The LIM domain protein nTRIP6 modulates the dynamics of myogenic differentiation - Tannaz Norizadeh Abbariki (Nature Portfolio, 2021)
Abstract The process of myogenesis which operates during skeletal muscle regeneration involves the activation of muscle stem cells, the so-called satellite cells. These then give rise to proliferating progenitors, the myoblasts which subsequently exit the cell cycle and differentiate into committed precursors, the myocytes. Ultimately, the fusion of myocytes leads to myofiber formation. Here we reveal a role for the transcriptional co-regulator nTRIP6, the nuclear isoform of the LIM-domain protein TRIP6, in the temporal control of myogenesis. In an in vitro model of myogenesis, the expression of nTRIP6 is transiently up-regulated at the transition between proliferation and differentiation, whereas that of the cytosolic isoform TRIP6 is not altered. Selectively blocking nTRIP6 function results in accelerated early differentiation followed by deregulated late differentiation and fusion. Thus, the transient increase in nTRIP6 expression appears to prevent premature differentiation. Accordingly, knocking out the Trip6 gene in satellite cells leads to deregulated skeletal muscle regeneration dynamics in the mouse. Thus, dynamic changes in nTRIP6 expression contributes to the temporal control of myogenesis.